Mechanical behavior of buried steel pipelines crossing strike-slip seismic faults - Vazouras, P.; Karamanos, S. A.; Dakoulas, P. (Volume 4: Pipeline and Riser Technology, 2011)
The present paper investigates the mechanical behaviour of buried steel pipelines, crossing active strike-slip tectonic faults. The fault plane is vertical and perpendicular to the pipeline axis. The interacting soil-pipeline system is modelled rigorously through finite elements, which account for large strains and displacements, nonlinear material behaviour and special conditions of contact and friction on the soil-pipe interface. Steel pipelines of various diameter-to-thickness ratios, and typical steel material for pipeline applications (API 5L grades X65 and X80) are considered. The paper investigates the effects of various soil and pipeline parameters on the mechanical response of the pipeline, with particular emphasis on pipe wall failure due to "local buckling" or "kinking" and pipe wall rupture. The effects of shear soil strength and stiffness, are also investigated. Furthermore, the influence of the presence of pipeline internal pressure on the mechanical response of the steel pipeline is examined. Numerical results aim at determining the fault displacement at which the pipeline failure occurs, and they are presented in a graphical form that shows the critical fault displacement, the corresponding critical strain versus the pipe diameter-to-thickness ratio. It is expected that the results of the present study can be used for efficient pipeline design in cases where active faults are expected to impose significant ground-induced deformation to the pipeline. Copyright © 2011 by ASME.